2001
DOI: 10.1007/pl00000020
|View full text |Cite
|
Sign up to set email alerts
|

Group and Individual Time Management Tools: What You Get is Not What You Need

Abstract: Some studies of diaries and scheduling systems have considered how individuals use diaries with a view to proposing requirements for computerised time management tools. Others have focused on the criteria for success of group scheduling systems. Few have paid attention to how people use a battery of tools as an ensemble. This interview study reports how users exploit paper, personal digital assistants (PDAs) and a group scheduling system for their time management. As with earlier studies, we find many shortcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 15 publications
1
69
0
1
Order By: Relevance
“…In our study of diary use (Blandford and Green, 2001), it was found that only four of the sixteen interviewees used the 'frequency' feature confidently and effectively; the other twelve reported never using it. Two of these reported simply remembering regular events or keeping a separate record of them, while the remaining ten chose to enter each event in the series separately.…”
Section: The Diary Systemmentioning
confidence: 71%
See 3 more Smart Citations
“…In our study of diary use (Blandford and Green, 2001), it was found that only four of the sixteen interviewees used the 'frequency' feature confidently and effectively; the other twelve reported never using it. Two of these reported simply remembering regular events or keeping a separate record of them, while the remaining ten chose to enter each event in the series separately.…”
Section: The Diary Systemmentioning
confidence: 71%
“…Diaries and their use have been extensively studied; for example, Kelley and Chapanis (1982), Kincaid, Dupont and Kaye (1985), Payne (1993) and Palen (1999) report on studies of diary use, and draw on those studies to propose recommendations for the design of new diary systems. In particular, Blandford and Green (2001) present results of a qualitative study of Meeting Maker, considering the role of the electronic diary within its social context of use, and also as one of a suite of time-management tools (including paper diaries and many other resources) that need to work well together. In that paper, we consider many aspects of usability; here, the focus is on particular features that are amenable to the modelling approach that is the subject of this paper.…”
Section: The Diary Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…It is often said that multi-tasking involves the management of a set of diverse aspects such as time, contacts, documents or even physical space (Belloti et al 2003;Blandford and Green 2001;Boardman and Sasse 2004). However, it is not clear how, in practice, individuals can juggle priorities and what strategies they use to achieve this.…”
Section: Related Workmentioning
confidence: 99%